Vehicle and Automotive Engineering 2 Proceedings of the 2nd VAE2018, Miskolc, Hungary - Jármai, Károly; Bolló, Betti; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the proceedings of the second Vehicle Engineering and Vehicle Industry conference, reflecting the outcomes of theoretical and practical studies and outlining future development trends in a broad field of automotive research. The conference's main themes included design, manufacturing, economic and educational topics.
Design -- Manufacturing -- Economy -- Education.
Keywords: Automotive engineering; Metals; Automotive Engineering; Metals and Alloys